Effect of oxytocin and cloprostenol on the seminal parameters of red brocket deer (Mazama rufa) during the electroejaculation procedure - Heredias-Ribas, Claudia Maria [UNESP]; Tanaka, Yuki [UNESP]; Duarte, Jose Mauricio Barbanti [UNESP] (Brazilian Coll Animal Reproduction, 2025)
Successful implementation of conservation programs for endangered species requires biological material for use in reproductive biotechnologies. This enhances reproductive efficiency and helps increase the populations of critically endangered species. One way to facilitate the exchange of genetics between captive and free-ranging animals is through the creation of cryogenic banks that store cryopreserved gametes. In particular, semen cryopreservation allows for this exchange to occur. We evaluated whether the use of exogenous hormones (such as oxytocin and prostaglandin) prior to electroejaculation increases seminal volume, sperm concentration, and the number of doses produced in the red brocket deer (Mazama rufa). We also evaluate whether seminal parameters vary over the three stimulation cycles of the same electroejaculation procedure. The treatments did not affect ejaculate volume (p = 0.402), the number of sperm cells in the ejaculates (p = 0.926), total doses produced (p = 0.684), sperm mass movement (p = 0.229), sperm cell concentration (p = 0.106), and acrosome integrity (p = 0.210). The use of hormones has potential in reducing the need for stressful stimuli in electroejaculation, but the choice of hormones must take into account their effects on semen quality.
Keywords: Cervidae; hormonal stimulation; red brocket deer; reproductive biotechnologies; semen collection.